2009
DOI: 10.2298/vsp0909738p
|View full text |Cite
|
Sign up to set email alerts
|

Poor outcome in patients with diffuse large B-cell lymphoma is associated with high percentage of bcl-2 and Ki 67-positive tumor cells

Abstract: An initial high IPI score associated with high Ki-67+ and bcl2+ could represent possible predictive factors of poor prognosis, which would help to identify a high risk subgroup of newly diagnosed DLBCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…However, we demonstrated a significant correlation between p16 hypermethylation and normal level of LDH and low/intermediate low IPI score. These two parameters have been related to better prognosis in many studies, which is confirmed for IPI in ours. To our knowledge, we are the first to detect such associations, so the importance of our results should be confirmed in the further studies on the larger number of samples.…”
Section: Discussionsupporting
confidence: 87%
“…However, we demonstrated a significant correlation between p16 hypermethylation and normal level of LDH and low/intermediate low IPI score. These two parameters have been related to better prognosis in many studies, which is confirmed for IPI in ours. To our knowledge, we are the first to detect such associations, so the importance of our results should be confirmed in the further studies on the larger number of samples.…”
Section: Discussionsupporting
confidence: 87%
“…The prognostic significance of Bcl-2 protein expression is controversial [5,6,7,8,9,10,13,19,20,26,27]. Some studies [8,9,10,20,27,28,30] showed that Bcl-2 protein overexpression was associated with poor OS, but some other studies [5,6,7,13,19,26] showed no difference in OS. Pervez et al reported positive Bcl-2 protein expression in 75 of 117 (64.1%) patients in their study on 117 patients with DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al [32] reported that tumor proliferation of >80.0% was associated with poorer survival in previously untreated patients with aggressive NHL, whereas Hall et al [35] found that patients who responded well to chemotherapy were less likely to relapse if they had >80.0% tumor proliferation. Jovanovic et al reported that the patients with a high proliferative fraction (Ki67 > 60.0%) had a worse OS rate with log-rank test analysis [30]. Conversely, Hasselblom et al found that patients with low Ki67 expression (<49.0%) had significantly worse progression-free survival and OS as independent risk factors [36].…”
Section: Discussionmentioning
confidence: 99%
“…The primary end point used in the determination of cutoff value was OS. Cut-off values for Bcl-2 was defined as 50% and Ki-67 was 75%, as was referred to the previous studies 26, 27.…”
Section: Methodsmentioning
confidence: 99%